Proximate Analysis and Hedonic Test on Dried Noodle with The Addition of Spirulina platensis Microalgae as A High Protein Food - Marcelinus Christwardana; Aniek Sri Handayani; Evita Febriyanti; H. Hadiyanto; Angela Nitia Nefasa (Diponegoro University, 2023)
The study focuses on malnutrition. Dietary intake influences malnutrition. Indonesians choose dry noodles due of their portability. Dry noodles often include more carbohydrates than protein; consequently, the addition of Spirulina platensis may increase their protein level while de-creasing their carbohydrate load. This research evaluated the levels of protein, fat, water, and ash in dry noodles before and after supplementation with spirulina platensis. 1% and 2% of the fixed variable weight of Spirulina platensis were used. Included in analyses are protein, fat, water, and ash. Variation I (1%) results protein of 15.79%, whereas Variation II (2%) has 28.21%. Variation I (1%) have 13.07% moisture, whereas Variation II (2%) has 13,15%. Variation I (1%) contain 0.233% fat compared to variation II (2%) of 0.223%. Variation I (1%) had 1.445% ash content, whereas Variation II (2%), contained 2% ash. The nutritional value of Grade II or dried noodles with Spirulina platensis conforms to Indonesian National Standard 8217-2015. Spirulina platensis increases the pro-tein content of dry noodles when added. According to SNI 8217-2015 grade II, the addition of spir-ulina to dried noodles improved their protein, water, ash, and fat content. The nutritious content of dried noodles was improved by the inclusion of Spirulina platensis.